2008
DOI: 10.5005/ijsm-3-1-14
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Persian Version of “BEARS” Pediatric Sleep Questionnaire

Abstract: Objective: To determine the reliability and validity of Persian version of "BEARS" (B=Bedtime Issues, E= Excessive Daytime Sleepiness, A=Night Awakenings, R=Regularity and Duration of Sleep, S=Snoring) pediatric sleep questionnaire. Setting: Two primary care pediatric clinics in Tehran, IRAN Methods: In the first step BEARS sleep questionnaire filled and in a 2 to 4 week period BEARS completed again (by another questioner) and all of the subjects visited by sleep specialists for diagnosis of sleep problem. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
11
1
Order By: Relevance
“…15 A positive answer to these questions is a sign of a child's sleep problems and prompts the physician to extract more information. Mohammadi et al (2008) reported good reliability and validity for the Persian version of this scale. 16 This questionnaire was used in our study to better estimate convergent validity.…”
Section: Bears Testmentioning
confidence: 91%
See 1 more Smart Citation
“…15 A positive answer to these questions is a sign of a child's sleep problems and prompts the physician to extract more information. Mohammadi et al (2008) reported good reliability and validity for the Persian version of this scale. 16 This questionnaire was used in our study to better estimate convergent validity.…”
Section: Bears Testmentioning
confidence: 91%
“…Mohammadi et al (2008) reported good reliability and validity for the Persian version of this scale. 16 This questionnaire was used in our study to better estimate convergent validity.…”
Section: Bears Testmentioning
confidence: 91%
“…Of these, the questionnaires of 250 children (130 boys and 120 girls) were usable for the data analysis. Iranian versions of two questionnaires, the Children's Sleep Habits questionnaire (CSHQ) 6,8,14,17 and BEARS (Bedtime problems, Excessive daytime sleepiness, Awakenings during the night, Regularity and duration of sleep and Snoring), 18 were completed by the interviewers. Bedtime problems in BEARS include resistance to going to bed and sleep onset latency (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…19 The BEARS sleep screening tool is divided into five major sleep domains, providing a comprehensive screen of the major sleep disorders affecting children aged 2-18 years. 18,20 Each sleep domain has a set of age-appropriate 'trigger questions' for use in the clinical interview. The CSHQ screens common sleep problems in children aged 2-12 years and consists of 33 items and 8 subscales.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation